2022
DOI: 10.1021/acsnano.2c03997
|View full text |Cite
|
Sign up to set email alerts
|

Twist Angle-Dependent Molecular Intercalation and Sheet Resistance in Bilayer Graphene

Abstract: Bilayer graphene (BLG) has a two-dimensional (2D) interlayer nanospace that can be used to intercalate molecules and ions, resulting in a significant change of its electronic and magnetic properties. Intercalation of BLG with different materials, such as FeCl3, MoCl5, Li ions, and Ca ions, has been demonstrated. However, little is known about how the twist angle of the BLG host affects intercalation. Here, by using artificially stacked BLG with controlled twist angles, we systematically investigated the twist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Thus, Figure 5 shows that our quasi-2D gold films are perfect candidates for flexible and transparent electrodes in optoelectronic applications. 23,41,42 , ITO 14,42 , and twisted graphene 43…”
Section: Morphology and Optoelectronic Properties Of Quasi-2d Gold Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Figure 5 shows that our quasi-2D gold films are perfect candidates for flexible and transparent electrodes in optoelectronic applications. 23,41,42 , ITO 14,42 , and twisted graphene 43…”
Section: Morphology and Optoelectronic Properties Of Quasi-2d Gold Filmsmentioning
confidence: 99%
“…Figure 5| Optoelectronic properties of quasi-2D gold. (a) Sheet resistance and transmittance at λ = 550 nm of quasi-2D gold in comparison with other ultrathin films23,41,42 , ITO14,42 , and twisted graphene43 . The inset zooms the transmittance-conductivity…”
mentioning
confidence: 99%
“…In particular, TBG exhibits superconductivity at a rotation angle of 1.1 • , which is called the magic angle [13,14]. It has also been reported that the rotation angle between graphene layers affects their optical properties [15,16], carrier mobility [17], and degree of molecular intercalation [18]. Thus, control of the rotation angle of graphene and other 2D materials is important for the development of their physics and applications.…”
Section: Introductionmentioning
confidence: 99%